First report of Brachymeria apicicornis (Cameron) (Hymenoptera, Chalcididae) on the curry leaf tortoise beetle Silana farinosa (Boheman) (Coleoptera, Chrysomelidae, Cassidinae, Cassidini) - Sabu, M. Sneha; Jaseel, R.; Karthika, S. (Journal of Plantation Crops, 2023)
Abstract. Silana farinosa (Boheman) (Coleoptera, Chrysomelidae, Cassidinae, Cassidini) is reported as the first confirmed host of Brachymeria apicicornis (Cameron) (Hymenoptera, Chalcididae). This is the first report of a natural enemy of the curry leaf tortoise beetle S. farinosa in India.